Economic analysis of tomato cultivation on dryland with drip irrigation technique - Suwati, Suwati; Muanah, Muanah; Huda, Ahmad Akromul; Gunawan, Adi (Jurnal Agrotek Ummat, 2022)
Economic analysis is one of the important parameters in applying drip irrigation techniques. For the community, this drip irrigation technique is a new technology so it needs to be analyzed with an economic approach. The purpose of this study was to analyze the economics of tomato cultivation by applying drip irrigation techniques on dry land. The research design used was a Randomized Block Design (RAK) with the following treatments, T1 (beds without mulch), T2, (beds with Straw mulch, and T3 (beds with silver-black plastic mulch). , production costs, farmer's income, and business feasibility by looking at the value of the B/C Ratio. Furthermore, the data from the analysis were tested using mathematical equations with the help of excel. The results of the analysis showed that the highest tomato production by applying drip irrigation techniques was found in T3 with a production yield of 896 quintals/ha with a total cost of IDR 369.000,000/ha, the highest level of income was also found in P3 of IDR 437,4000,000/ha and the highest B/C Ratio value was also found in T3, namely 1.18. So based on the results and discussion it can be concluded that economically for tomato cultivation by applying drip irrigation techniques should use bed cover using mulch a Silver Black Plastic.